DISASTER PREVENTION AND MITIGATION QUALITY OF SERVICE OF THA MAI RUAK SUBDISTRICT MUNICIPALITY, THA YANG DISTRICT, PHETCHABURI PROVINCE - Korudomchoke, Thadarat; Adultutra, Suchart; Maitreesophon, Bampen (Journal of MCU Phetchaburi Review, 2025)
This mixed-method research aimed to 1) study the quality of disaster prevention and mitigation services of Tha Mai Ruak Subdistrict Municipality, 2) compare the quality of disaster prevention and mitigation services of Tha Mai Ruak Subdistrict Municipality classified by individual characteristics, 3) study the service factors affecting the quality of disaster prevention and mitigation services of Tha Mai Ruak Subdistrict Municipality, and 4) propose guidelines for developing the quality of disaster prevention and mitigation services of Tha Mai Ruak Subdistrict Municipality. The sample consisted of 400 people in Tha Mai Ruak Subdistrict and 12 key informants. Data were analyzed using percentages, means, standard deviations, one-way variance, multiple regression, and content analysis. The results of the study found that 1) the quality of disaster prevention and mitigation services, overall and in each aspect, was at the highest level. 2) Individual characteristics, such as different incomes, had different opinions on the quality of disaster prevention and mitigation services. 3) All overall service factors affected the quality of disaster prevention and mitigation services. Statistically significant at the 0.001 level. 4) Guidelines for developing the quality of disaster prevention and relief services of Tha Mai Ruak Subdistrict Municipality found that development should be made in the matter of checking equipment and tools to ensure readiness for use. There should be the same standard for providing services. Regulations and laws should be studied precisely. There should be a clear plan for various operations. Training should be organized to provide comprehensive knowledge. An understanding of providing services in various situations should be created.